Sequence stratigraphy and uranium mineralization model of uranium-bearing rock series in the southern margin of Erlian Basin - Zhao Yue; Shao Longyi; Xu Qiang; Zhao Xin; Wang Jianxin; Ding Rong (矿业科学学报, 2018)
Based on drilling data, seismic sections and sample test results, the theory of continental to sequence stratigraphy was applied to investigate uranium accumulation of the Early Cretaceous uranium-bearing rock series in the southern margin of Erlian Basin.Four sequence boundaries, such as the regional unconformity surface, the erosional base of incise valley, sedimentary facies association transform suface and palaeontology characteristics have been identified, which subdivide the Early Cretaceous uranium-bearing rock series into three third-order sequences and corresponding low-order system tract, lake-invaded system tract and high-level system tract.Three types of sedimentary facies and of the meandering river, braided river delta and lacustrine seven sedimentary microfacies are mainly developed in the study area, and the uranium-bearing rocks are mainly delta plain interdistributary bay and marsh facies.The sandy conglomerate in the meandering river bed developed in the sequence Ⅲ controls the distribution of uranium mineralization.The dark organic-rich mudstone and carbonaceous mudstone developed in the transgressive system of the sequenceⅡ are the main enrichment of uranium deposits, which belongs to the typical dive-oxidized uranium mineralization.On this basis, the compound-phreatic oxidative metallogenic model was established.The research results above can not only provide guidance for the classification and correlation of sequence stratigraphy in the studied area but improve the development of the uranium control factors in the rift basin.